PENGAMBILAN KEPUTUSAN SECARA KOLEKTIF OLEH PIMPINAN KPK BERDASARKAN PASAL 21 AYAT (5) UNDANG-UNDANG NOMOR 30 TAHUN 2002 TENTANG KOMISI PEMBERANTASAN KORUPSI - Putri Kemala Sari (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2019)
Article 21 paragraph (5) of the Corruption Eradication Commission Law states that the Chairperson of the Corruption Eradication Commission "works collectively", which in the explanation stated that each decision making must be approved and decided together. The main problem of this research is about the pre-trial case of Budi Gunawan which was determined by the suspect by the KPK in the arguments of the petitioner's petition stating that the suspect's determination was not carried out collectively because at that time there was a vacancy of one of the KPK Leaders. Therefore this study aims to examine and examine the decision-making process by the KPK Leaders as the application of Article 21 paragraph (5) of the KPK Law and also determine the scope of tasks that are collectively decided and agreed upon together. This study uses a normative juridical method. The research specifications used are descriptive analytical, using a statute-approach approach, conceptual approach and comparative approach. The results of the study can be summarized as follows: First, the collective decision-making process is carried out in the form of ordinary mechanisms, formal mechanisms and urgent mechanisms. With the decision making procedure carried out by deliberation to reach consensus and use the most votes (voting) as stated in Commission Regulation No. 3 of 2009 concerning the procedures for decision making by the KPK leadership, but in the provisions of Article 7 PK / 3/2009 formulate that decision making can be carried out in less than 3 (three) people (not fulfilling the quorum) in the event of an urgent situation, and meaning the collective "by the KPK is not always interpreted as making decisions in its entirety (the five leaders), then the provision overrides the actual collective meaning based on the principle of working collectively. Second, as for the scope of the collective decision-making tasks by the KPK Leaders regulated in Article 3 CHAPTER III LEADERSHIP Regulation No. 1 of 2015 concerning the Organization and Work Procedure of the KPK, it is stated that the increase in the status of suspects is the scope of tasks decided and agreed collectively with expose procedure. Keywords: komisi pemberatasan korupsi, pengambilan keputusan, keputusan kolektif